The effect of perception of organizational support and compensation on teacher performance with organizational citizenship behavior (OCB) as intervening variables - Putri Azizi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The Effect of Perception of Organizational Support and Compensation on Organizational Citizenship Behavior (OCB) and how much influence organizational support perception, compensation, and organizational citizenship behavior (OCB) influences on teacher performance. The method of collecting data through surveys and distributing questionnaires, with a sample of 35 respondents. The Sampling technique is using saturated sampling techniques by making the entire population into samples. The analytical methods used are correlation analysis, multiple linear regression and path analysis using SPSS 21. The results of the study obtained based on partial test (Test t) obtained perception of organizational support and compensation partially significantly affect organizational citizenship behavior (OCB) in junior high school 2 (SMP Negeri 2) Ranah Batahan, West Pasaman Regency. Based on the Simultaneous Test (Test F) obtained the Perception of Organizational Support and Compensation together has a significant effect on Organizational Citizenship Behavior (OCB) in SMP Negeri 2 Ranah Batahan, West Pasaman Regency. And also the results of research based on Partial Test (Test T) obtained, Perception of Organizational Support, Compensation and Organizational Citizenship Behavior (OCB) partially significantly affect teacher performance in SMP Negeri 2 Ranah Batahan, West Pasaman Regency. And based on simultaneous tests (Test F) obtained perception of organizational support, compensation and organizational citizenship behavior (OCB) together has a significant effect on teacher performance in junior high school 2 (SMP Negeri 2) Ranah Batahan, West Pasaman Regency.